Dissociation of Survival, Proliferation, and State Control in Human Hematopoietic Stem Cells - Knapp, David J.H.F. (Stem Cell Reports, 2017)
The role of growth factors (GFs) in controlling the biology of human hematopoietic stem cells (HSCs) remains limited by a lack of information concerning the individual and combined effects of GFs directly on the survival, Mitogenesis, and regenerative activity of highly purified human HSCs. We show that the initial input HSC activity of such a purified starting population of human cord blood cells can be fully maintained over a 21-day period in serum-free medium containing five GFs alone. HSC survival was partially supported by any one of these GFs, but none were essential, and different combinations of GFs variably stimulated HSC proliferation. However, serial transplantability was not detectably compromised by many conditions that reduced human HSC proliferation and/or survival. These results demonstrate the dissociated control of these three human HSC bio-responses, and set the stage for future improvements in strategies to modify and expand human HSCs ex vivo.